2021
DOI: 10.1186/s12879-021-05862-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparing mortality between positive and negative blood culture results: an inverse probability of treatment weighting analysis of a multicenter cohort

Abstract: Background The association between blood culture status and mortality among sepsis patients remains controversial hence we conducted a tri-center retrospective cohort study to compare the early and late mortality of culture-negative versus culture-positive sepsis using the inverse probability of treatment weighting (IPTW) method. Methods Adult patients with suspected sepsis who completed the blood culture and procalcitonin tests in the emergency de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The major infection sites were grouped as the lower respiratory tract, urinary tract and abdominal infection, and the minor sites were grouped as isolated blood stream infection, skin and soft tissue infection, and the central nervous system. 17 The collected data include demographics, underlying diseases, initial vital signs, infection sites, and clinical outcomes, such as ICU admission, duration of ICU stay and expenditure, and mechanical ventilation requirements. The date of the patient's death was obtained from the hospital's electronic medical record system.…”
Section: Data Collection and Definition Of Variablesmentioning
confidence: 99%
“…The major infection sites were grouped as the lower respiratory tract, urinary tract and abdominal infection, and the minor sites were grouped as isolated blood stream infection, skin and soft tissue infection, and the central nervous system. 17 The collected data include demographics, underlying diseases, initial vital signs, infection sites, and clinical outcomes, such as ICU admission, duration of ICU stay and expenditure, and mechanical ventilation requirements. The date of the patient's death was obtained from the hospital's electronic medical record system.…”
Section: Data Collection and Definition Of Variablesmentioning
confidence: 99%
“…In conclusion, several clinical and laboratory variables showed promising predictive possibilities for mortality, with sepsis among them. To our knowledge, our study is the first observational study demonstrating increased mortality risk in calves with sepsis, a contested topic in human medicine 55‐61 …”
Section: Discussionmentioning
confidence: 89%
“…To our knowledge, our study is the first observational study demonstrating increased mortality risk in calves with sepsis, a contested topic in human medicine. [55][56][57][58][59][60][61] Information on bacteria involved in sepsis and their antimicrobial resistance profile is limited, especially in Europe. Therefore, our second objective was to obtain knowledge on the bacteria involved in sepsis in critically ill calves and their antimicrobial susceptibility.…”
Section: Bacteria and Antimicrobial Resistancementioning
confidence: 99%
“…Recently, Liu et al . using the inverse probability of treatment weighting method to investigate the impact of positive blood culture on 30 and 90-day mortality among 1405 patients with suspected sepsis, found that blood culture-positive patients had similar 30-day mortality but higher 90-day mortality than those in culture-negative patients [ 16 ]. The aforementioned data showed that culture positivity appears to be associated with long-term outcomes instead of short-term outcomes; therefore, there is an essential need for studies focusing on long-term outcomes in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have explored the association between culture positivity, a positive microbial culture of clinical samples during admission, and mortality in critically ill patients, but the evidence appeared to be inconclusive due to high heterogeneity among studies, with the majority of studies explored the short-term impact of culture positivity among patients with sepsis in the medical ICU [ 12 14 ]. Few studies, including our previous study focusing on 638 patients with cancer receiving perioperative intensive care, have found that culture positivity tended to be associated with 1-year mortality instead of short-term mortality [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%